THE EFFECTIVENESS OF JIGSAW STRATEGY TO IMPROVE STUDENTS' SKILLS IN WRITING A RECOUNT TEXT - Sitohang, Iranita (2013)
This research is intended to find out how Jigsaw can improve students' skill in writing a recount text. It was conducted at a vocational school in Bandung, involving students of eleventh grade as the participants. The research is a quasi-experimental design. In this study, the data of the study were obtained through questionnaire, pre-test and post-test. Data obtained from questionnaire were analyzed in order to investigate students' opinion about the challenges of writing a recount text. The data from pre-test and post-test were analyzed by using independent t-test from SPSS 20.0 program for windows. Based on the findings, the challenges faced by students in writing a recount text is the use of past tense, limited vocabulary, and shematic structure of recount text. The quantitative finding of the study shows that significance value is lower than 0.05 (p = 0.000 < 0.05), which indicates that Jigsaw can improve students' writing skill in the class investigated. Jigsaw helps students to deal with their inability of writing a recount text because each student gives support to their member in home group in order to gain their group's achievement. In addition, Jigsaw helps students to gather more knowledge when sharing the information and knowledge of their part in the expert group. It is suggested that further researcher investigates the use Jigsaw in writing other texts genre. Keywords: Jigsaw, Recount text, Writing, Methodology